1997
DOI: 10.1126/science.278.5339.853
|View full text |Cite
|
Sign up to set email alerts
|

Metal Ion Chaperone Function of the Soluble Cu(I) Receptor Atx1

Abstract: Reactive and potentially toxic cofactors such as copper ions are imported into eukaryotic cells and incorporated into target proteins by unknown mechanisms. Atx1, a prototypical copper chaperone protein from yeast, has now been shown to act as a soluble cytoplasmic copper(I) receptor that can adopt either a two- or three-coordinate metal center in the active site. Atx1 also associated directly with the Atx1-like cytosolic domains of Ccc2, a vesicular protein defined in genetic studies as a member of the copper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

27
676
2
8

Year Published

1999
1999
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 657 publications
(713 citation statements)
references
References 23 publications
27
676
2
8
Order By: Relevance
“…It is therefore suspected that in Menkes' disease patients, the absence of this ATPase prevents some form of copper transport. Researchers study ing the MNK homolog from yeast, Co2+-SENSITIVE CROSS-COMPLEMENTER2 (CCC2), found the product of this gene in the membranes of post-Golgi vesicles [IZ], and found that it forms part of a specific copper-delivery pathway [13] (Figure la). CCCZ was found to interact with a cyto plasmic copper chaperone, ANTIOXIDANTl (ATXl) [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is therefore suspected that in Menkes' disease patients, the absence of this ATPase prevents some form of copper transport. Researchers study ing the MNK homolog from yeast, Co2+-SENSITIVE CROSS-COMPLEMENTER2 (CCC2), found the product of this gene in the membranes of post-Golgi vesicles [IZ], and found that it forms part of a specific copper-delivery pathway [13] (Figure la). CCCZ was found to interact with a cyto plasmic copper chaperone, ANTIOXIDANTl (ATXl) [13].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers study ing the MNK homolog from yeast, Co2+-SENSITIVE CROSS-COMPLEMENTER2 (CCC2), found the product of this gene in the membranes of post-Golgi vesicles [IZ], and found that it forms part of a specific copper-delivery pathway [13] (Figure la). CCCZ was found to interact with a cyto plasmic copper chaperone, ANTIOXIDANTl (ATXl) [13]. Through this interaction, copper is transferred from ATXl to CCCZ and then into the lumen of the post-Golgi vesicle.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro (Achila et al 2006;Banci et al 2008Banci et al , 2009aPufahl et al 1997;Wernimont et al 2000) and in silico (Rodriguez-Granillo et al 2010) work has shown that Cu transfer from Atox1 to metal-binding domains of ATP7A/B proceeds via Cu-bridged hetero-dimer complexes where the metal is shared between the two metal-binding sites (Fig. 2).…”
Section: Moving Cu From Chaperone To Atp7a/bmentioning
confidence: 99%
“…2). Cu is thought to move from one protein to the other via ligand-exchange reactions involving tri-coordinated Cu-sulfur intermediates (Pufahl et al 1997). All six domains of ATP7A/B can be loaded with Cu by Atox1 but only in some cases, have Cu-dependent protein-protein complexes been detected by NMR via slower tumbling times (Achila et al 2006;Banci et al 2005Banci et al , 2008Banci et al , 2009a.…”
Section: Moving Cu From Chaperone To Atp7a/bmentioning
confidence: 99%
“…ATP7A and 7B, which are both found in the trans-Golgi network, contain six MxCxxC metal binding domains (MBDs) at their amino termini and each MBD is capable of binding one atom of copper [53]. Antioxidant protein 1, or Atox1 (Atx1 in yeast) is a cytosolic copper chaperone responsible for the shuttling of Cu (I) to ATP7A and 7B [54][55][56][57]. Following binding to copper and under normal or low copper conditions, ATP7A and 7B translocate Cu (I) into the lumen of the secretory vesicles for integration into cuproenzymes such as ceruloplasmin and tyrosinase [58,59].…”
Section: Copper Metabolism In Eukaryotic Cellsmentioning
confidence: 99%